Influencia del monitoreo y acompañamiento pedagógico directivo en el desempeño docente de instituciones educativas públicas del nivel primaria distrito Iquitos 2023 - Leal Cahuaza, María Elena (2025)
This section presents the most important research. In terms of the study carried out to explain the influence of monitoring the management accompaniment for the teaching performance in public primary educations institutions, district of Iquitos 2023. In the methodological framework, explanatory research was used with a field design, causal and transversal correlations, a questionnaire and an observation form were used as instruments, which were validated through judgment of experts. The population was structured by 585 teachers from 26 public institutions in the urban area of the Iquitos district from which a sample of 306 teachers from 9 educational institutions of the primary level. The results obtained using the appropriate statistics assume the alternative hypothesis (Ha), which confirms the existence of significant influence among the study variables.